Evaluation of STAT3 rs1053004 single nucleotide polymorphism in patients with chronic hepatitis B and hepatocellular carcinoma - Fatemipour, Maryam; Arabzadeh, Seyed Ali Mohammad; Molaei, Hamdireza; Geramizadeh, Bita; Dabiri, Shahryar; Fatemipour, Bahareh; Vahedi, Seyed Mahdi; Malekpour Afshar, Reza (Cellular and Molecular Biology, 2017)
Chronic infection with hepatitis B (CHB) virus is one of the most important risk factors for Hepatocellular carcinoma (HCC). Hepatitis B virus (HBV) causes liver cancer in various ways. One of these ways is increasing the expression of the signal transducer and activator of transcription 3 (STAT3) in Hepatocytes by HBV. The purpose of this research is to evaluate the single nucleotide polymorphism (SNP) rs1053004 in the STAT3 gene in CHB patients and individuals who suffer from HCC. In this research, 33 patients CHB-related HCC, 50 patients infected with chronic hepatitis B infection (CHB) without HCC and 50 healthy individuals were investigated for the presence of rs1053004 in the STAT3 gene according to the PCR-based differentiation of alleles test. Data analysis presented a different and significant distribution of alleles and genotypes (p<0.05). When the HCC and CHB groups were compared from the point of the frequency of alleles, the frequency of the C allele and CC genotype in the HCC group were higher CHB and control groups. Analysis of our data in the genotype model (CC vs. TT + TC) showed, this meaningful relationship remained between the HCC group and the three groups of CHB, healthy and all controls. These results illustrate that perhaps rs1053004 polymorphisms in the STAT3 gene participated in the progression of hepatitis B to HCC in Iranian people.